Robótica educacional: desafios e possibilidades no ensino de matemática no Qui lombo de bom Jardim - Santarém/Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
Currently, in the educational media, alternatives are sought that will promote the development of new activities related to the introduction of new pedagogical techniques that aim to contribute to the permanence and greater performance in student learning. In the specific case of educational robotics, it is expected that it contributes as a technique for improvement in the teaching of mathematics, considering that this range of knowledge presents a high degree of difficulty in practically all levels of education. Teaching through the use of technological resources is already a reality in our society, however, not all students and schools have access to these technologies, especially in the case of quilombola school education, after all, most communities are removed from the urban area, schools often do not have adequate structure for quality education, thus causing some students to migrate to neighboring communities or to the city, causing the loss of their cultural identity. For this reason, the present work intends to provide pedagogical experiences from robotic devices, with students of the 9th grade of elementary school of the Municipal School of Early Childhood and Elementary School São Pedro do quilombo de Bom Jardim, located in the rural area in the municipality of Santarém PA, thus being able to develop possible links between the teaching of mathematics and information technologies. I situate this research in approaches proposed by authors such as Araújo and Mafra, Maliuk and Zilli that highlight the importance of the use of technology in education, considering the development of operational activities for the teaching and learning of Mathematics, the assembly of prototypes and programming with the software of Lego Mindstorms EV3. In relation to the main results found, the use of educational robotics allowed us to enrich, in a collaborative way, stimulate and develop several competencies in our participants. Thus, those who intend to use this proposal in their future applications will only need to be motivated and observe the need of each student in the school environment, given that there is a clear need for methodological changes in vertical education that is still predominant in our educational system.
Keywords: Educação matemática; Robótica educacional; Educação Quilombola